(3dSGf GdYQHs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s
(3ChdgG (B:s
(3bGd YHO Gddg eMeO Hf GdecQe GdMeO ddg QH GdYGdejf JHQckG HaGJMI dcJGH GdYRjR hEfi de CRd eTahYkG HeWGdYGJ cJH GddZGJ hde CNQL ajg YeG ai gPg GdCUhd , hQJHJg JQJjH HUMGM ai GdCHhGH hGdaUhd s
(3BNQgG (B:s
(3BNQ GdehLhO efgG CKfGA eGOI QhM bhdg (B: (3hGdQhM GJSGY eG Hjf GdaNOjf Ch SYI ai GdQLdjf hQLd CQhM hbO QhMJ bOeg QhMkG s
(3hLO HChdgG HNW eZGjQ JQLeI dGHf efXhQ efbhdI ef HZjI GdhYGI ddSjhWis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B108 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B46s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B192 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GddZIs